Investigations into crazing in glassy amorphous polymers through molecular dynamics simulations. (April 2015) - Venkatesan, Sudarkodi; Basu, Sumit
Abstract: In many glassy amorphous polymers, localisation of deformation during loading leads to crazes. Crazes are crack like features whose faces are bridged either by fibrils or a cellular network of voids and fibrils. While formation of crazes is aided by the presence of surface imperfections and embedded dust particles, in this work, we focus on intrinsic crazes that form spontaneously in the volume of the material. We perform carefully designed molecular dynamics simulations on well equilibrated samples of a model polymer with a view to gaining insights into certain incompletely understood aspects of the crazing process. These include genesis of the early nanovoids leading to craze nucleation, mechanisms of stabilising the cellular or fibrillar structure and the competition between chain scission and chain disentanglement in causing the final breakdown of the craze. Additionally, we identify and enumerate clusters of entanglement points with high functionality as effective topological constraints on macromolecular chains. We show that regions with low density of entanglement clusters serve as sites for nanovoid nucleation under high mean stress. Growth occurs by the repeated triggering of cavitation instabilities above a growing void. The growth of the void is aided by disentanglement in and flow of entanglements away from the cavitating region. Finally, for the chain lengths chosen, scission serves to supply short chains to the growing craze but breakdown occurs by complete disentanglement of the chains. In fact, most of the energy supplied to the material seems to be used in causing disentanglements and very little energy is required to create a stable fibril. Abstract : Graphical abstract: Abstract : Highlights: Crazing in amorphous glassy polymers was studied using Molecular dynamics simulations. A new technique for quantifying entanglements was proposed. Identification of mechanics of nano-cavitation leading to intrinsic craze initiation. Exploration of conditions leading to cellular or fibrillar morphology of craze growth. Study of relative contribution of scission and disentanglement on craze failure.